MEDICINAL FORMULATIONS OF A KANDA TRIBAL HEALER – A TRIBE ON THE VERGE OF DISAPPEARANCE IN BANGLADESH - Rahmatullah, Mohammed; Ayman, Umma; Akter, Fatema; Sarker, Mridul; Sifa, Rolee; Sarker, Bijoy; Chyti, Humayra Naj; Jahan, Farhana Israt; Chowdhury, Majeedul H; Chowdhury, Soheli A (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The Kanda tribe is one of the lesser known small tribes of Bangladesh with an estimated population of about 1700 people (according to them), and on the verge of extinction as a separate entity. To some extent, they have assimilated with the surrounding mainstream Bengali-speaking population, but they still maintain their cultural practices including traditional medicinal practices, for which they have their own tribal healers. Nothing at all has been documented thus far about their traditional medicinal practices and formulations, which are on the verge of disappearance. The Kanda tribe can be found only in scattered tea gardens of Sreemangal in Sylhet district of Bangladesh; dispersion of the tribe into small separated communities is also contributing to the fast losing of traditional medicinal practices. The objective of the present study was to conduct an ethnomedicinal survey among the traditional healers of the Kanda tribe (in fact, only one such healer was found after extensive searches). Information was collected from the healer with the help of a semi-structured questionnaire and the guided field-walk method. A total of 24 formulations were obtained from the healer containing 34 plants including two plants, which could not be identified. Besides medicinal plants, the Kanda healer also used the body hairs of the Asiatic black bear (Ursus thibetanus) and bats (Pteropus giganteus giganteus) in one of his formulation for treatment of fever with shivering. The ailments treated by the Kanda healer were fairly common ailments like cuts and wounds, skin diseases, helminthiasis, fever, respiratory problems (coughs, asthma), gastrointestinal disorders (stomach pain, constipation, diarrhea), burning sensations during urination, various types of pain (headache, body ache, toothache, ear ache), conjunctivitis, poisonous snake, insect or reptile bites, jaundice, and bone fractures. A number of important drugs in allopathic medicine like quinine, artemisinin, and morphine (to name only a few) have been discovered from observing indigenous medicinal practices. From that view point, the formulations used by the Kanda healer merit scientific studies for their potential in the discovery of cheap and effective new drugs. Scientific validation of the medicinal formulations of the Kanda healer can also be effective for treatment of ailments among this tribe, which does not have or does not want to have any contact with modern medicine.